Intelligence Fuzzy Logic System to Diagnosis and Control Spark Ignition Engines - Nekooei, Mohammad Javad; Pauzi, M. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
Air pollution is one of the important challenging issues these days that researchers have been trying to maintain it in a normal range. The emissions of vehicle engine exhausts are responsible for fifty percent of air pollution. There is a tendency to develop of engine control which works in a simple way. in this paper a simple fuzzy logic (FL) control has been developed which is used for defining engine system faults and control and maintain them in a normal range without use any complicated mathematical equation and any fault sensor.